Rutile-configuration CoSb2O6 catalyst as well as preparation method and application thereof

By preparing the rutile-configured CoSb2O6 catalyst on a titanium substrate, and using the electronic configuration of the antimony to regulate the catalyst, the problem of high prices caused by the use of precious metals in traditional catalysts is solved, and efficient and stable production of propylene oxide is achieved, reducing production costs.

CN119710785APending Publication Date: 2025-03-28TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510102778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The high use of precious metals in traditional catalysts leads to high prices, and in Cl-mediated electrochemical propylene epoxidation, the stability and product selectivity of the catalyst are difficult to meet industrial needs.

Method used

A rutile-configured CoSb2O6 catalyst was developed, and catalyst electrodes were prepared on a titanium substrate by electrodeposition and high-temperature annealing. The electron configuration of the catalyst was regulated by the introduction of antimony, and the adsorption of the reaction medium and the generation of active species were promoted.

Benefits of technology

In Cl-mediated electrochemical propylene epoxidation, the production of propylene oxide is achieved efficiently and stably, and the catalytic activity, product selectivity and stability reaches 83.38%, reducing the production cost of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710785A_ABST
    Figure CN119710785A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical propylene epoxidation electrodes, and discloses a rutile configuration CoSb2O6 catalyst and a preparation method and application thereof, and the catalyst is used for electrodepositing a CoSb2O6 electrode on a titanium substrate; the preparation process comprises the following steps: firstly, polishing the titanium substrate to remove an oxide layer on the surface, and then etching with an oxalic acid solution to form a uniform gray surface; cleaning and drying the etched titanium plate for later use; and further selecting a deposition potential, carrying out electro-deposition on the titanium substrate in a deposition solution containing cobalt chloride and antimony potassium tartrate to obtain a Co (OH) 2 / Sb precursor film, and finally annealing in an air atmosphere at a specific temperature for a specific time to obtain the CoSb2O6 electrode. The CoSb2O6 electrode with a rutile structure is synthesized by introducing Sb, adsorption of a reaction medium on the surface of the electrode is promoted, combination of generated active species and reactants is facilitated, and the CoSb2O6 electrode shows excellent catalytic activity, product selectivity and stability in application of Cl-mediated electrochemical propylene epoxidation to preparation of epoxypropane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical propylene epoxidation electrodes, and in particular, relates to a CoSb2O6 catalyst with a rutile configuration, a preparation method thereof, and an application thereof in promoting the generation of propylene oxide. Background Art

[0002] Propylene oxide (PO) is an important industrial intermediate that can be converted into a variety of commercial chemicals, such as polyurethane foams, polymers, propylene carbonate, propylene glycol, etc. (1,2,3). The global PO market size was estimated to be US$22.9 billion in 2022 and is expected to reach US$35.2 billion by 2030. Making full use of renewable electricity from sustainable energy sources to drive electrochemical epoxidation reactions is expected to produce PO chemicals in a more environmentally friendly and mild manner to meet the requirements of achieving the dual carbon strategy goals. In recent years, the electrochemical chlorohydrin process has attracted much attention as a more sustainable and potentially cost-effective alternative (4,5). The Cl ions in the electrochemical chlorohydrin process act as redox mediators, which can promote the indirect electron transfer process between the electrode and the reaction substrate, extend the reaction system to the entire bulk electrolyte, overcome mass transfer limitations, and avoid over-oxidation. If the abundant chloride in seawater can be used for chloride ion-mediated propylene epoxidation, it will produce greater product benefits.

[0003] The mechanism of electrochemical chlorohydrin epoxidation is the coupling of a heterogeneous direct electron transfer process and a homogeneous redox reaction. The halogen ions first undergo a 2-electron oxidation reaction on the catalyst surface to be converted into halogen molecules, which then combine with the organic substrate to undergo a homogeneous chemical reaction. Specifically, in electrochemical epoxidation using chloride ions as the medium, how to design and regulate the catalyst structure to ensure the efficient and stable generation of active chlorine species in the heterogeneous reaction has become the first key issue that researchers need to consider. Specifically, in a 2022 work, the Sargent group targeted the problem of hypochlorous acid hydrolysis. By loading BaO2 on IrO2, the catalyst was modified to increase the thermodynamic potential for the cracking of hypochlorous acid on the surface of the modified catalyst, thereby improving the Faradaic efficiency of ethylene oxide (6). Wang et al. designed a single-atom Ru-doped KIrRuO nanowire catalyst for the efficient production of ethylene oxide in the chlorine-mediated ethylene epoxidation process. The ethylene oxide partial current density of the KIrRuO catalyst is as high as 0.7 Acm -2 , with a yield as high as 92.0% (7).

[0004] Currently, most catalyst materials used are still precious metals such as Ir and Ru. The scarcity of raw materials also leads to the high price of such catalysts (8,9,10). Secondly, we need to consider how to regulate the adsorption and desorption of chlorine species so as to ensure that the product selectivity and energy utilization rate reach the optimal value in the electrochemical test. Moreover, Cl - The corrosion problem will also lead to instability in the industrial scale-up production process. Therefore, it is urgent to develop electrocatalytic materials with clear structure, excellent performance and low price.

[0005] 1. Herzberger, J.; Niederer, K.; Pohlit, H.; Seiwert, J.; Worm, M.; Wurm, FR; Frey, H., Polymerization of Ethylene Oxide, Propylene Oxide, and Other Alkylene Oxides:Synthesis, Novel Polymer Architectures,andBioconjugation.Chem.Rev.2015,116(4),2170-2243.

[0006] 2. Ke, J.; Zhao, J.; Chi, M.; Wang, M.; Kong,

[0007] 3. Ko, M.; Kim, Y.; Woo, J.; Lee, B.; Mehrotra, R.; Sharma, P.; Kim, J.; Hwang, SW; Jeong, HY; Lim, H.; Joo, SH; Jang, J.-W.; Kwak, JH. Direct propylene epoxidation with oxygen using a photo-electro-heterogeneous catalyticsystem.Nat.Catal.2021,5(1),37-44.

[0008] 4.Leow,W.R.;Lum,Y.;Ozden,A.;Wang,Y.;Nam,D.-H.;Chen,B.;Wicks,J.;Zhuang,T.-T.;Li,F.;Sinton,D.;Sargent,E.H.,Chloride-mediated selectiveelectrosynthesis of ethylene and propylene oxides at high currentdensity.Science 2020,368(6496),1228–1233.

[0009] 5.Chung,M.;Jin,K.;Zeng,J.S.;Manthiram,K.,Mechanism of Chlorine-Mediated Electrochemical Ethylene Oxidation in Saline Water.ACS Catal.2020,10(23),14015-14023.

[0010] 6.Li,Y.;Ozden,A.;Leow,W.R.;Ou,P.;Huang,J.E.;Wang,Y.;Bertens,K.;Xu,Y.;Liu,Y.;Roy,C.;Jiang,H.;Sinton,D.;Li,C.;Sargent,E.H.,Redox-mediatedelectrosynthesis of ethylene oxide from CO2 and water.Nat.Catal.2022,5(3),185-192.

[0011] 7.Wang,H.;Wang,S.;Song,Y.;Zhao,Y.;Li,Z.;Shen,Y.;Peng,Z.;Gao,D.;Wang,G.;Bao,X.,Boosting Electrocatalytic Ethylene Epoxidation by Single AtomModulation.Angew.Chem.,Int.Ed.2024,63(20),e202402950.

[0012] 8. Wang, J.; Wu, G.; Feng, G.; Li, G.; Wei, Y.; Li, S.; Mao, J.; Liu, X.; Chen, A.; Song, Y.; Dong, X.; Wei, W.; Chen, W., Electrochemical Epoxidation of Propylene to Propylene Oxide via Halogen-Mediated Systems.ACS Omega 2023,8(49),46569-46576.

[0013] 9. Huang, L.; Wang, P.; Jiang, Y.; Davey, K.; Zheng, Y.; Qiao, S.-Z., EthyleneElectrooxidation to2-Chloroethanol in Acidic Seawater with Natural ChlorideParticipation.J.Am.Chem.Soc.2023,145(28),15565-15571.

[0014] 10. Zhu, W.; Song, Ru enhance the acidic oxygen evolution reactionactivity in two-dimensional ruthenium-iridium oxide.Nat.Commun.2023,14(1),5365. Summary of the invention

[0015] The present invention aims to solve the problem that traditional catalysts use a large amount of precious metals, which leads to high prices. It provides a rutile-structured CoSb2O6 catalyst and its preparation method and application. By means of electrodeposition and further high-temperature annealing, the CoSb2O6 catalyst electrode is uniformly prepared on a titanium substrate. The introduction of antimony promotes the adsorption of the reaction medium on the electrode surface, which is conducive to the generation of active species that combine with reactants. - The mediated electrochemical propylene epoxidation to propylene oxide exhibits excellent catalytic activity, product selectivity and stability.

[0016] In order to achieve the above-mentioned object of the invention, the present invention is implemented by the following technical solutions:

[0017] According to one aspect of the present invention, a rutile-configuration CoSb2O6 catalyst is provided, comprising a titanium substrate and a catalyst thin film electrode, wherein the catalyst thin film electrode is a rutile-configuration CoSb2O6 electrode.

[0018] According to another aspect of the present invention, a method for preparing the above-mentioned rutile-structured CoSb2O6 catalyst is provided, and the method is carried out according to the following steps:

[0019] (1) After etching the titanium substrate, cleaning, drying and setting aside;

[0020] (2) fixing the titanium substrate obtained in step (1) with an electrode clamp, immersing it in a deposition solution containing cobalt chloride, potassium antimony tartrate and potassium nitrate, and depositing a Co(OH)2 / Sb precursor film based on Coulomb termination under a three-electrode system;

[0021] (3) In an air atmosphere, annealing the Co(OH)2 / Sb precursor film obtained in step (2) at a temperature of 500-700°C for 6-8 hours; after the sample is cooled to room temperature, a rutile CoSb2O6 electrode is obtained.

[0022] Furthermore, the etching treatment of step (1) is as follows: the commercial titanium substrate is polished with sandpaper to remove the oxide layer on the surface, and then cut into electrode size; etching is performed with a 10-20% mass fraction oxalic acid solution at a temperature of 100-120° C. for 2-3 hours to form a uniform gray surface; after cooling to room temperature, the titanium substrate is removed.

[0023] Furthermore, the titanium substrate after etching in step (1) is cleaned with pure water, dried and placed in anhydrous ethanol for later use.

[0024] Furthermore, the molar concentration ratio of cobalt chloride, potassium antimony tartrate and potassium nitrate in the deposition solution of step (2) is 4:1:40.

[0025] Furthermore, in the three-electrode system described in step (2): the titanium plate is the working electrode, the iridium ruthenium oxide is the counter electrode, and the Ag / AgCl (saturated KCl) is the reference electrode.

[0026] Furthermore, the deposition potential in step (2) is -0.9V to -1.3V vs. Ag / AgCl.

[0027] According to another aspect of the present invention, there is provided a rutile-structured CoSb2O6 catalyst in Cl -Application of mediated electrochemical propylene epoxidation to propylene oxide.

[0028] Furthermore, the rutile CoSb2O6 catalyst is used as a working electrode, the Ag / AgCl electrode is used as a reference electrode, and the Pt sheet is used as a counter electrode, and they are assembled into an electrochemical cell; C3H6 is continuously introduced into the electrochemical cell, and power is applied to carry out an electrocatalytic reaction.

[0029] The beneficial effects of the present invention are:

[0030] The rutile-structured CoSb2O6 catalyst of the present invention can obtain a CoSb2O6 film with a more stable structure. The dense arrangement of rutile crystals can effectively inhibit the Cl - The penetration of antimony improves the intrinsic stability of the catalyst; and the reaction kinetics are significantly improved by doping with antimony, so that excellent propylene epoxidation activity is obtained both in natural seawater and simulated electrolyte.

[0031] The preparation method of the rutile-configuration CoSb2O6 catalyst of the present invention uses the titanium substrate obtained by pretreatment in the early stage as the catalyst substrate, and then uses cobalt chloride and potassium antimony oxytartrate as cobalt sources and antimony sources, and obtains the rutile-configuration CoSb2O6 catalyst by electrodeposition and further high-temperature annealing. The raw materials required in the preparation process are simple, the preparation method is simple and easy, and batch preparation can be realized, which has certain industrial prospects.

[0032] The rutile-structured CoSb2O6 catalyst of the present invention is used for Cl - The mediated electrochemical epoxidation of propylene to propylene oxide, the Co and Sb in the catalyst act synergistically, the introduction of Sb regulates the electronic configuration of the catalyst, accelerates the reaction kinetics, and is conducive to Co as an active site to adsorb free Cl in the electrolyte - The active chlorine species thus formed further reacted with the reactant propylene to promote the formation of the target product propylene oxide, achieving a propylene oxide Faraday efficiency of 83.38%. - The mediated electrochemical epoxidation of propylene to propylene oxide exhibits excellent catalytic activity, product selectivity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a schematic diagram of the electrodeposition described in Examples 1-7;

[0034] Figure 2 XRD diffraction spectrum of the Co(OH)2 / Sb precursor film prepared in Example 1-5;

[0035] Figure 3 XRD spectra and scanning electron microscope images of the CoSb2O6 electrodes prepared in Examples 1-5;

[0036] Figure 4 XRD spectrum and scanning electron microscope image of the Co3O4 electrode prepared in Example 6;

[0037] Figure 5 XRD spectrum and scanning electron microscope image of the Sb2O3 electrode prepared in Example 7;

[0038] Figure 6 is the Cl corresponding to Example 8 - Concentration versus FE of propylene oxide;

[0039] Figure 7 It is a comparison chart of LSV test of Example 1, Example 6, Example 7 and Co(OH)2 / Sb precursor film corresponding to Example 8 in 0.5M NaCl electrolyte;

[0040] Figure 8 This is the liquid phase nuclear magnetic spectrum of the Co(OH)2 / Sb precursor film prepared in Example 1 corresponding to Example 8 after epoxidation test;

[0041] Fig. 9 This is the liquid phase nuclear magnetic spectrum of the Sb2O3 electrode prepared in Example 7 corresponding to Example 8 after epoxidation test;

[0042] Fig.10 This is a stability test diagram of the CoSb2O6 electrode prepared in Example 2 corresponding to Example 8 in 0.5M NaCl electrolyte;

[0043] Fig.11 This is a stability test diagram of the Co3O4 electrode prepared in Example 6 corresponding to Example 8 in 0.5M NaCl electrolyte; Fig.12 A comparison chart of electrochemical kinetic experiments of CoSb2O6 and Co3O4 electrodes prepared in Examples 5 and 6 corresponding to Example 8 in 0.5M NaCl electrolyte;

[0044] Fig.13 This is a comparison of in-situ Raman spectra of CoSb2O6 and Co3O4 electrodes prepared in Examples 5 and 6 corresponding to Example 8 in 0.5M NaCl electrolyte;

[0045] Fig.14 This is a graph showing the electrochemical epoxidation performance of the CoSb2O6 electrode prepared in Example 5 corresponding to Example 8 in simulated seawater and natural seawater electrolytes. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0047] like Figure 1 As shown, some preferred embodiments of the present invention prepare rutile CoSb2O6 catalysts according to the following steps:

[0048] (1) A commercial titanium plate is sanded to remove the oxide layer on the surface, and then cut into an electrode size of 25 mm×10 mm×0.2 mm; it is etched with a 10-20% mass fraction oxalic acid solution at a temperature of 100-120° C. for 2-3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate is taken out; the obtained titanium plate is washed with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for standby use;

[0049] (2) fixing the titanium substrate obtained in step (1) with an electrode clamp, immersing it in a deposition solution containing cobalt chloride, potassium antimony tartrate and potassium nitrate in a molar concentration ratio of 4:1:40, and obtaining a Co(OH)2 / Sb precursor film under a three-electrode system with a titanium plate as a working electrode, iridium ruthenium oxide as a counter electrode, and Ag / AgCl (saturated KCl) as a reference electrode at a deposition potential of -0.9 V to -1.3 V vs. Ag / AgCl based on a charge of 3.6C;

[0050] (3) Under air atmosphere, annealing the Co(OH)2 / Sb precursor film obtained in step (2) in a muffle furnace at 500-700°C for 6-8 hours; after the sample is cooled to room temperature, a rutile CoSb2O6 electrode is obtained.

[0051] The rutile-structured CoSb2O6 catalyst of the present invention is - In the application of mediated electrochemical propylene epoxidation to propylene oxide, a rutile CoSb2O6 catalyst is used as a working electrode, an Ag / AgCl electrode is used as a reference electrode, and a Pt sheet is used as a counter electrode, which are assembled into an electrochemical cell; C3H6 is continuously introduced into the electrochemical cell, and power is applied to carry out an electrocatalytic reaction.

[0052] Example 1

[0053] Preparation of etched titanium plate

[0054] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 10 wt.% oxalic acid solution at 100°C for 2 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0055] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0056] Preparation of CoSb2O6 electrode

[0057] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride, 10 mM potassium antimony tartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 / Sb precursor film was obtained at a potential of -0.9 V vs. Ag / AgCl based on a charge of 3.6 C.

[0058] (4) The Co(OH)2 / Sb precursor film obtained above was annealed in a muffle furnace at 500°C for 6 hours under air atmosphere; after the sample was cooled to room temperature, a CoSb2O6 electrode with a rutile configuration was obtained.

[0059] Figure 2 The X-ray diffraction spectrum (XRD) of the unannealed Co(OH)2 / Sb precursor film prepared in Example 1; Figure 2 It can be seen that the XRD spectrum can only obtain the diffraction peak of the titanium substrate, indicating that the Co(OH)2 / Sb precursor film without high-temperature annealing is phase-separated Co(OH)2 and elemental Sb, and the whole presents an amorphous structure.

[0060] Figure 3 a is the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 1; Figure 3 It can be seen in a that the diffraction peak of the CoSb2O6 electrode completely matches the standard card of CoSb2O6 (PDF#18-0403), indicating that CoSb2O6 with good crystallinity was obtained.

[0061] Figure 3 b is a scanning electron microscope image of the high temperature annealed CoSb2O6 electrode prepared in Example 1; Figure 3 As can be seen in b, CoSb2O6 is tightly packed, so it can effectively inhibit Cl - The penetration of ions improves the corrosion resistance of the catalyst.

[0062] Example 2

[0063] Preparation of etched titanium plate

[0064] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 10 wt.% oxalic acid solution at 110°C for 3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0065] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0066] Preparation of CoSb2O6 electrode

[0067] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride, 10 mM potassium antimony tartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 / Sb precursor film was obtained at a potential of -1.0 V vs. Ag / AgCl based on a charge of 3.6 C.

[0068] (4) The Co(OH)2 / Sb precursor film obtained above was annealed in a muffle furnace at 600°C for 6 hours under an air atmosphere; after the sample was cooled to room temperature, a CoSb2O6 electrode with a rutile configuration was obtained.

[0069] The diffraction peaks of the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 2 completely match the standard card of CoSb2O6 (PDF#18-0403), indicating that CoSb2O6 with good crystallinity is obtained.

[0070] Example 3

[0071] Preparation of etched titanium plate

[0072] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 10 wt.% oxalic acid solution at 120°C for 3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0073] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0074] Preparation of CoSb2O6 electrode

[0075] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride, 10 mM potassium antimony tartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 / Sb precursor film was obtained at a potential of -1.1 V vs. Ag / AgCl based on a charge of 3.6 C.

[0076] (4) The Co(OH)2 / Sb precursor film obtained above was annealed in a muffle furnace at 700°C for 6 hours under air atmosphere; after the sample was cooled to room temperature, a CoSb2O6 electrode with a rutile configuration was obtained.

[0077] The diffraction peaks of the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 3 completely match the standard card of CoSb2O6 (PDF#18-0403), indicating that CoSb2O6 with good crystallinity is obtained.

[0078] Example 4

[0079] Preparation of etched titanium plate

[0080] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 20 wt.% oxalic acid solution at 120°C for 2 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0081] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0082] Preparation of CoSb2O6 electrode

[0083] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride, 10 mM potassium antimony tartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 / Sb precursor film was obtained at a potential of -1.2 V vs. Ag / AgCl based on a charge of 3.6 C.

[0084] (4) The Co(OH)2 / Sb precursor film obtained above was annealed in a muffle furnace at 600°C for 7 hours under air atmosphere; after the sample was cooled to room temperature, a rutile CoSb2O6 electrode was obtained.

[0085] The diffraction peaks of the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 4 completely match the standard card of CoSb2O6 (PDF#18-0403), indicating that CoSb2O6 with good crystallinity is obtained.

[0086] Example 5

[0087] Preparation of etched titanium plate

[0088] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with 20 wt.% oxalic acid solution at 120°C for 3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0089] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0090] Preparation of CoSb2O6 electrode

[0091] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride, 10 mM potassium antimony tartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 / Sb precursor film was obtained at a potential of -1.3 V vs. Ag / AgCl based on a charge of 3.6 C.

[0092] (4) The Co(OH)2 / Sb precursor film obtained above was annealed in a muffle furnace at 600°C for 8 hours under air atmosphere; after the sample was cooled to room temperature, a CoSb2O6 electrode with a rutile configuration was obtained.

[0093] The diffraction peaks of the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 5 completely match the standard card of CoSb2O6 (PDF#18-0403), indicating that CoSb2O6 with good crystallinity is obtained.

[0094] Example 6

[0095] Preparation of etched titanium plate

[0096] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 10 wt.% oxalic acid solution at 110°C for 3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0097] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0098] Preparation of Co3O4 electrode

[0099] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 40 mM cobalt chloride and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Co(OH)2 precursor film was obtained at a potential of -1.3 V vs. Ag / AgCl based on a charge of 3.6 C.

[0100] (4) The Co(OH)2 precursor film obtained above was annealed in a muffle furnace at 600°C for 6 hours under an air atmosphere; after the sample was cooled to room temperature, a rutile Co3O4 electrode was obtained.

[0101] Figure 4 a is the XRD spectrum of the high temperature annealed CoSb2O6 electrode prepared in Example 6; Figure 4 It can be seen in a that the diffraction peak of the Co3O4 electrode completely matches the standard card of Co3O4 (PDF#42-1467), indicating that Co3O4 with good crystallinity was obtained.

[0102] Figure 4 b is a scanning electron microscope image of the high temperature annealed Co3O4 electrode prepared in Example 6; Figure 4 As can be seen in b, Co3O4 appears in the shape of nanorods.

[0103] Example 7

[0104] Preparation of etched titanium plate

[0105] (1) A commercial titanium plate of 100 mm × 100 mm × 0.2 mm was sanded to remove the oxide layer on the surface, and then cut into 25 mm × 10 mm × 0.2 mm sizes, and etched with a 10 wt.% oxalic acid solution at 110°C for 3 hours to form a uniform gray surface; after cooling to room temperature, the titanium plate was taken out.

[0106] (2) The titanium plate obtained in step (1) is cleaned with pure water, dried to obtain an etched titanium substrate, and placed in anhydrous ethanol for later use.

[0107] Preparation of Sb2O3 electrode

[0108] (3) The titanium substrate obtained above was fixed with an electrode clamp and immersed in a deposition solution containing 10 mM potassium antimony oxytartrate and 400 mM potassium nitrate. The titanium plate was used as the working electrode, iridium ruthenium oxide was used as the counter electrode, and Ag / AgCl (saturated KCl) was used as the reference electrode. The Sb precursor film was obtained at a potential of -1.3 V vs. Ag / AgCl based on a charge of 3.6 C.

[0109] (4) The Sb precursor film obtained above was annealed in a muffle furnace at 600° C. for 6 hours under air atmosphere; after the sample was cooled to room temperature, a rutile Sb2O3 electrode was obtained.

[0110] Figure 5 a is the XRD spectrum of the high temperature annealed Sb2O3 electrode prepared in Example 7; Figure 5 It can be seen in a that the diffraction peak of the Sb2O3 electrode completely matches the standard card of Sb2O3 (PDF#05-0534), indicating that Sb2O3 with good crystallinity was obtained.

[0111] Figure 5 b is a scanning electron microscope image of the high temperature annealed Sb2O3 electrode prepared in Example 7; Figure 5 As can be seen in b, Sb2O3 presents a polyhedral configuration.

[0112] Example 8

[0113] The catalysts prepared in Examples 1-7 were subjected to Cl - Performance test of mediated electrochemical propylene epoxidation to propylene oxide.

[0114] The CoSb2O6 electrode was used as the working electrode (electrode area 2 cm 2 ), Ag / AgCl electrode as reference electrode, Pt sheet as counter electrode to assemble electrochemical cell, and Cl - Mediated electrochemical propylene epoxidation test and electrode stability test. The electrolyte is a NaCl solution saturated with C3H6. C3H6 is continuously introduced into the electrochemical cell during the reaction, and the product is quantitatively detected by liquid phase nuclear magnetic resonance.

[0115] Since the rate-determining step of propylene epoxidation to propylene oxide is Cl - Adsorption related, Cl - The concentration will affect the reaction rate and thus the catalytic activity. - The activity test was carried out under the concentration conditions to select the optimal Cl - concentration.

[0116] The Faradaic Efficiency (FE) of the propylene oxide product of the CoSb2O6 catalyst prepared in Example 1 in 0.1M, 0.5M, 1M, and 3M NaCl electrolytes at an applied potential of 1.55V vs Ag / AgCl is shown in Tables 1 and Figure 6 The results show that when Cl - When the concentration is 0.5M, the FE of PO reaches the highest. - Concentration, due to Cl - Insufficient supply leads to incomplete reaction and reduced yield. - As the concentration increases further, the FE of PO also decreases gradually. It is speculated that the excess Cl - Unfavorable for the reversible disproportionation reaction of Cl2 and H2O Thus, the formation of HClO is inhibited.

[0117] Table 1

[0118]

[0119] The results of linear sweep voltammetry (LSV) tests of Example 1, Example 6, Example 7 and the uncalcined Co(OH)2 / Sb precursor film in 0.5M NaCl electrolyte are shown in FIG. Figure 7 As shown in Figure 2, the CoSb2O6 electrode has a lower starting potential and a higher current density than the Co3O4 electrode. However, the Co(OH)2 / Sb precursor film and Sb2O3 are not conductive.

[0120] The uncalcined Co(OH)2 / Sb precursor film prepared in Example 1 was used to test its catalytic activity in 0.5M NaCl electrolyte. The amorphous Co(OH)2 / Sb precursor film had no catalytic activity, which was also confirmed by the liquid phase nuclear magnetic resonance results after the reaction. Figure 8 shown.

[0121] The catalytic activity of the CoSb2O6 catalyst prepared in Example 2-5 was tested in 0.5M NaCl electrolyte at different voltages. The FE of PO is shown in Table 2.

[0122] Table 2.1

[0123]

[0124] Table 2.2

[0125]

[0126]

[0127] Table 2.3

[0128]

[0129] Table 2.4

[0130]

[0131] Table 2.1 is a graph showing the propylene epoxidation performance of the CoSb2O6 electrode prepared in Example 2. The experimental results show that the optimal FE of PO for the CoSb2O6 electrode prepared in Example 2 is 83.38%.

[0132] Table 2.2 is a graph showing the propylene epoxidation performance of the CoSb2O6 electrode prepared in Example 3. The experimental results show that the optimal FE of PO for the CoSb2O6 electrode prepared in Example 3 is 73.02%.

[0133] Table 2.3 is a graph showing the propylene epoxidation performance of the CoSb2O6 electrode prepared in Example 4. The experimental results show that the optimal FE of PO for the CoSb2O6 electrode prepared in Example 4 is 75.43%.

[0134] Table 2.4 is a graph showing the propylene epoxidation performance of the CoSb2O6 electrode prepared in Example 5. The experimental results show that the optimal FE of PO for the CoSb2O6 electrode prepared in Example 5 is 77.43%.

[0135] The catalytic activity of the Co3O4 and Sb2O3 catalysts prepared in Examples 6-7 was tested in 0.5M NaCl electrolyte at different voltages. The FE of PO of the Co3O4 electrode is shown in Table 3. The Sb2O3 electrode has no catalytic activity, which is also confirmed by the liquid phase nuclear magnetic resonance results after the reaction. Fig. 9 shown.

[0136] Table 3

[0137]

[0138] The stability test results of the CoSb2O6 electrode prepared in Example 2 and the Co3O4 electrode prepared in Example 6 in 0.5M NaCl electrolyte are as follows: Fig.10 , Fig.11 The results show that compared with the Co3O4 electrode, the CoSb2O6 electrode with the introduction of Sb can effectively inhibit the penetration of Cl- ions due to its compact stacking, enhance the corrosion resistance of the catalyst, and thus show better stability.

[0139] The results of electrochemical kinetic experiments using the CoSb2O6 and Co3O4 electrodes prepared in Examples 5-6 in 0.5M NaCl electrolyte are shown in Fig.12 The Tafel slope of CoSb2O6 is much smaller than that of Co3O4, indicating that the introduction of Sb greatly improves the reaction kinetics. Fig.13 The in situ Raman results show that the Sb-deficient Co3O4 electrode has slower kinetics than the CoSb2O6 electrode and needs to be driven at a higher potential to drive the electrochemical epoxidation reaction. These Raman results complement the electrochemical kinetics experiments, demonstrating that the addition of Sb greatly reduces the kinetic potential of the reaction and accelerates the epoxidation process.

[0140] The electrochemical epoxidation performance of the CoSb2O6 electrode prepared in Example 5 in simulated seawater and natural seawater electrolytes is shown in FIG. Fig.14 The CoSb2O6 electrode still exhibits a comparable FE, with 1-chloro-2-propanol as the main product.

[0141] In summary, the present invention develops a cheap and readily available catalyst synthesis method to solve the problem of Cl - The catalyst materials in the field of mediated electrochemical propylene epoxidation are single, high cost, and not resistant to Cl - Corrosion and other problems. By introducing Sb into Co-based oxides, a CoSb2O6 electrode with a rutile configuration was synthesized, which improved the thermodynamic stability of the catalyst. The catalyst exhibited catalytic activity comparable to that of precious metal catalysts, with a FE of up to 83.38% at 1.55V vs.Ag / AgCl. The electrochemical kinetic results also showed that the introduction of Sb significantly accelerated the reaction rate of the CoSb2O6 electrode compared with Co3O4. This enhancement was further confirmed by in situ Raman spectroscopy. In addition, the system has wide applicability in the field of seawater electrolysis for PO4 production.

[0142] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A rutile CoSb2O6 catalyst, characterized in that: It comprises a titanium substrate and a catalyst thin film electrode, wherein the catalyst thin film electrode is a CoSb2O6 electrode of rutile configuration.

2. A method for preparing the rutile CoSb2O6 catalyst as claimed in claim 1, characterized in that: The method proceeds as follows: (1) After etching the titanium substrate, cleaning, drying and setting aside; (2) fixing the titanium substrate obtained in step (1) with an electrode clamp, immersing it in a deposition solution containing cobalt chloride, potassium antimony tartrate and potassium nitrate, and depositing a Co(OH)2 / Sb precursor film based on Coulomb termination under a three-electrode system; (3) In an air atmosphere, annealing the Co(OH)2 / Sb precursor film obtained in step (2) at a temperature of 500-700°C for 6-8 hours; after the sample is cooled to room temperature, a rutile CoSb2O6 electrode is obtained.

3. The method for preparing the rutile CoSb2O6 catalyst according to claim 2, characterized in that: The etching treatment of step (1) is as follows: the commercial titanium substrate is polished with sandpaper to remove the oxide layer on the surface, and then cut into electrode size; etching is performed with a 10-20% mass fraction oxalic acid solution at a temperature of 100-120° C. for 2-3 hours to form a uniform gray surface; after cooling to room temperature, the titanium substrate is removed.

4. The method for preparing the rutile CoSb2O6 catalyst according to claim 2, characterized in that: After the etching treatment in step (1), the titanium substrate is cleaned with pure water, dried and placed in anhydrous ethanol for later use.

5. The method for preparing the rutile CoSb2O6 catalyst according to claim 2, characterized in that: The molar concentration ratio of cobalt chloride, potassium antimony tartrate and potassium nitrate in the deposition solution of step (2) is 4:1:

40.

6. The method for preparing the rutile CoSb2O6 catalyst according to claim 2, characterized in that: In the three-electrode system described in step (2): the titanium plate is the working electrode, the iridium ruthenium oxide is the counter electrode, and the Ag / AgCl (saturated KCl) is the reference electrode.

7. The method for preparing the rutile CoSb2O6 catalyst according to claim 2, characterized in that: The deposition potential in step (2) is -0.9V to -1.3V vs. Ag / AgCl.

8. A rutile CoSb2O6 catalyst as claimed in claim 1 in Cl - Application of mediated electrochemical propylene epoxidation to propylene oxide.

9. The rutile CoSb2O6 catalyst according to claim 8 is used in Cl - The invention relates to an application of a mediated electrochemical propylene epoxidation to produce propylene oxide, characterized in that: The rutile CoSb2O6 catalyst is used as a working electrode, the Ag / AgCl electrode is used as a reference electrode, and the Pt sheet is used as a counter electrode, and they are assembled into an electrochemical cell; C3H6 is continuously introduced into the electrochemical cell, and electricity is applied to carry out an electrocatalytic reaction.

Citation Information

Patent Citations

  • Catalyst for synthesizing acrylonitrile and process for producing acrylonitrile

    CN101530806A

  • Crystalline cobalt antimonate coating titanium electrode and preparation method thereof

    CN116162956A

  • Preparation method of novel titanium-based SnO2 anode

    CN117509832A

  • Oxidation catalyst and process for preparing unsaturated acids aldehydes and nitriles

    GB1510854A

  • Antimonate electrocatalyst for an electrochemical reaction

    US20200188898A1